Resilience at the workplace: A systematic review and meta-analysis of mindfulness-based, cognitive-behavioural, and multimodal interventions - Quintana, Larissa Melina Pereira (2023)
Dissertação de Mestrado em Psicologia do Trabalho, das Organizações e dos Recursos Humanos apresentada à Faculdade de Psicologia e de Ciências da Educação